Решите уравнение:5х-3/9-4х+3/6=х-1

Решите уравнение:5х-3/9-4х+3/6=х-1
Гость
Ответ(ы) на вопрос:
Гость
(5х - 3)/9 - (4х + 3)/6 = х - 1 2(5x - 3)/18 - 3(4x + 3)/18 = x - 1 (10x - 6 - 12x - 9)/18 = x - 1 - 2x - 15 = 18x - 18 20x = 3 x = 3 : 20 x = 0,15 Проверим:  (5*0,15 - 3)/9 - (4*0,15 + 3)/6 = 0,15 - 1                          (0,75 - 3)/9 - 3,6/6 = - 0,85                          -4,5/18 - 10,8/18 = - 0,85                            -153/180 = - 0,85                                 - 0,85 = - 0,85           
Не нашли ответ?
Ответить на вопрос
Похожие вопросы